Analysis of chromatin and nuclear area alterations in triatomines during starvation - Casseb-Hassan, Patrícia Martins; Santos, Adriana Barbosa; Oliveira, Maria Tercília Vilela de Azeredo [UNESP] (Firenze University Press, 2001)
In the present study changes in nuclear area and chromatin distribution in the Malpighian tubules of a blood-feeding insect, the vector of Chagas' disease were analysed. Male and female adult insects were dissected, after a starving period of up to 28 days. The Malpighian tubules were fixed and stained by orcein lacto-acetic. The nuclei were analyzed by photomicrography, karyometry and a statistical analysis was performed. It was observed that with the increase of the starvation period there were alterations in the nuclear phenotype, that is, changes in the nuclear area and chromatin extenuation. In males, starting from the second week of starvation, chromatin extenuation was accentuated, and the beginning of nuclear coalition occurred more frequently in the third and fourth starvation weeks. In females, the accentuated chromatin extenuation was observed after the third starvation week, and irregularities in nuclear borders were more frequent. The descriptive statistical analysis of the male and temale nuclear areas revealed that the nuclear areas continued to increase during starvation reaching highest values in the third week. Another outstanding aspect is that in the third starvation week karyometry presented larger heterogeneity with higher standard deviation values for both genders. Therefore, nuclear alterations related to the distribution and extenuation chromatin and increase in nuclear area were observed. These aspects suggest the presence of nuclear metabolic mechanisms that lead to synthesis of specific proteins necessary for the protection and maintenance of the cell during physiologic stress.
Keywords: Chromatin; Malpighian tubules; Nuclear area; Rhodnius prolixus; Starvation; Triatomines